Rechtsschenkelblock, Linksschenkelblock, Schrittmacher bei akutem Koronarsyndrom – kann man das EKG hier vergessen? - Grautoff, Steffen (DMW - Deutsche Medizinische Wochenschrift, 2017)
The 12 lead ECG is difficult to evaluate if there is a persistent right or even left bundle block or a pace maker continually stimulating the right ventricle. Despite these pre-existing or new ECG changes it might still be possible to detect variations which can hint to an ST-elevation myocardial infarction (STEMI). Diagnosing significant ST elevations in a case of right bundle block is not very challenging. If the ECG shows a left bundle block the modified Sgarbossa criteria should be used for evaluation. These criteria can also be used in a pace maker ECG. If a patient is not pacemaker-dependent the stimulation can be paused transiently to reveal changes of the ST segment. At first medical contact it can be very important to assess these changes correctly in order to classify the ECG as a STEMI.
Keywords: 12-Kanal-EKG; Rechtsschenkelblock; Linksschenkelblock; Schrittmacherrhythmus; Sgarbossa-Kriterien